Individual and Collective Posttraumatic Growth in Victims of Natural Disasters: A Multidimensional Perspective - Wlodarczyk, Anna (2017)
This study set out to incorporate the collective dimensions of posttraumatic growth and examined the construct and predictive validity of The Individual and Collective Posttraumatic Growth Scale (ICPTGS). Participants were 332 volunteers who had experienced the earthquake on February 27, 2010, in Chile. Analysis allowed us to confirm a multidimensional structure composed of four dimensions: individual, spiritual, communal growth, and societal growth. Additionally, we identified association among ICPTGS, perceived emotional impact, and social well-being. This study emphasizes that positive changes resulting from the exposure to collective disasters can be perceived also at the collective or community level.